Research on the Flexible Grid-connected / Islanded Control Strategy of Ship Power Supply Converter Based on State Feedback - WU Yi; WANG Yue; ZHOU Zhenbang; PENG Yun; HU Jingyu (Kongzhi Yu Xinxi Jishu)
In order to realize the flexible switching and controllable power transfer between the ship power supply converter and shore power, this paper proposes a mode switching control method based on grid-connected/islanded control state feedback, which realizes the fast response of output voltage in off-grid mode and controllable transfer of interaction power in grid-connected mode. Secondly, based on the presynchronous control of amplitude modulation and frequency modulation, the smooth transition between given current command and voltage control PI regulator is realized. The flexible grid-connected/islanded control of power supply converter is realized. Finally, the simulation results of a ship power converter verify that the proposed control method can suppress the oscillation and smooth output, and make the specific unbalance of current less than 5%.